EKSPLORASI KETERKAITAN KONDISI KEUANGAN PEMERINTAH DAERAH DENGAN TINGKAT LAYANAN PENDIDIKAN - Biizni Putri Bengi (ABIS: Accounting and Business Information Systems Journal, 2019)
ABSTRACTPurpose – This study aims to explore the lingkage between the financial condition of local government and education service level in cluster two of local government. Methodology –The financial condition of local government are measured using dimension that related to services that given by local government, this dimension is service level solvency. This dimension consists of two ratios, expenditure ratio and asset ratio. The level of education services is measured using achievement indicators contained in the minimum education service standard (SPM). This study uses a descriptive qualitative method. Secondary data were collected through documentation technique and the primary data were collected through semi-strutured interview technique.Findings – The findings in this study showed that there is no linkage between the financial conditions of local governments and the level of education services. interviews were conducted to confirm how the involvement of local governments in the planning and budgeting processes in the regions, priorities that form the basis of budgeting and factors that influence the achievement of minimum service standards (SPM). The results of interview data analysis indicate that the involvement of the local education office (dinas pendidikan) in the planning and budgeting process in the local government is quite good, and minimum service standards are one of the bases in budgeting. Furthermore, the factors that influence the achievement of minimum service standards are human resource capacity, stakeholder awareness and budgeting capabilities in the education unit.